Prognostic significance of adjuvant therapy and specific radiation dosages in Taiwanese patients with oral cavity cancer and extra-nodal extension: a nationwide cohort study - Tsai, Yao-Te; Chen, Wen-Cheng; Wen, Yu-Wen; Lin, Chien-Yu; Fan, Kang-Hsing; Lin, Jin-Ching; Ng, Shu-Hang; Lee, Shu-Ru; Kang, Chung-Jan; Lee, Li-Yu; Chien, Chih-Yen; Hua, Chun-Hung; et al. (BMC cancer, 2024)
The evidence for adjuvant chemoradiotherapy (CRT) of oral cavity squamous cell carcinoma (OCSCC) with extra-nodal extension (ENE) in National Comprehensive Cancer Network (NCCN) guidelines is derived from patients with head and neck cancer. The guidelines further suggest a radiation dose ranging from 6000 to 6600 cGy. In this nationwide study, we sought to evaluate the prognostic significance of adjuvant therapy and the specific radiation dosage in Taiwanese patients with pure OCSCC and ENE. A retrospective analysis of 1577 OCSCC patients with ENE who underwent resection and received adjuvant CRT or radiotherapy (RT) between January 2011 and December 2020 was conducted. Multivariable analysis revealed that adjuvant RT, more than four pathologically positive nodes, and radiation dosage below 6000 cGy were independent risk factors for unfavorable 5-year disease-specific survival (DSS) and overall survival (OS). Comparing patients who received CRT (n = 1453) to those treated with RT (n = 124) before and after propensity score (PS) matching, the 5-year outcomes were as follows: before PS matching, DSS (54% versus 30%, p < 0.0001), OS (42% versus 18%, p < 0.0001); after PS matching (n = 111 in each group), DSS (52% versus 30%, p = 0.0016), OS (38% versus 21%, p = 0.0019). For patients who underwent CRT, the 5-year outcomes for different radiation dose groups (6600 - 7000 cGy, n = 1155 versus 6000 - 6500 cGy, n = 199) were as follows: before PS matching, DSS (52% versus 54%, p = 0.1904), OS (43% versus 46%, p = 0.1610); after PS matching (n = 199 in each group), DSS (55% versus 54%, p = 0.8374), OS (46.5% versus 46.3%, p = 0.7578). For OCSCC patients with ENE, our study shows CRT improved survivals than RT alone, underscoring the clinical significance of chemotherapy. Patients undergoing CRT with irradiation doses ranging from 6000 to 6500 cGy exhibited comparable survival outcomes to those receiving doses of 6600-7000 cGy. This observation suggests that irradiation doses exceeding the 6600 cGy may not confer the survival advantage in these patients. Further research is needed to confirm our results and explore the optimal irradiation dose for managing these patients.